2021
DOI: 10.1007/s10853-021-05812-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinant parameters of surface morphology to corrosion behaviour of cold-rolled auto sheet steel

Abstract: To elucidate the effect of surface morphology on corrosion behaviour of coldrolled steel, three-dimensional (3D) surface profiles, average corrosion rate and potential differences (PD) for local areas of cold-rolled steel were investigated using a 3D white-light interference surface profilometer, polarization curves and atomic force microscope. Results showed that the linear relationship between surface roughness Sa and corrosion rate, achieved based on polished steels, was not valid for the as-received inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Chen et al [8] determined that the depth of the valleys on the material surface was effective in the corrosion process of IF (interstitialfree) steel in a 3.5 wt% NaCl solution and they stated that it affected the average corrosion rate of IF steel. Cui et al [15] concluded that peaks and valleys on the surface of the material may cause corrosion by forming galvanic cells. Wei et al [16] used composite material in their study and stated that the type of corrosion occurring in this material changed from general corrosion to pitting as the surface roughness decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [8] determined that the depth of the valleys on the material surface was effective in the corrosion process of IF (interstitialfree) steel in a 3.5 wt% NaCl solution and they stated that it affected the average corrosion rate of IF steel. Cui et al [15] concluded that peaks and valleys on the surface of the material may cause corrosion by forming galvanic cells. Wei et al [16] used composite material in their study and stated that the type of corrosion occurring in this material changed from general corrosion to pitting as the surface roughness decreased.…”
Section: Introductionmentioning
confidence: 99%